Off-campus teaching supervisory practices in some selected public elementary schools of Isabela - Apostol, Lolita (Lim) 1932- (s.n.], 1968)
The purpose of the study is to determine the supervisory practices of the off-campus student teaching staff in selected public elementary schools in Isabela.